Candidaemia among Adult Solid Organ Transplant Recipients. (July 2018) - Yesilkaya, Aysegul; Demirkaya, Melike H.; Ozalp, Onur; Ayvazoglu Soy, Ebru H.; Azap, Ozlem Kurt; Arslan, Hande; Haberal, Mehmet
Abstract : Introduction: To evaluate the local epidemiology, Candida species distribution and compare the distribution, demographic, clinical characteristics and outcome of candidaemia episodes in between Candida albicans and non-albicans Candida (NAC) candidaemia episodes among adult solid organ transplantation (SOT) recipients. Materials and Methods: The medical records for each adult SOT recipient from January 2007 to August 2014 were evaluated. Candidaemia was defined as at least one blood culture positive for a Candida species in patients with clinically apparent signs and symptoms of infection. The interval betweeen two seperate candidaemia episodes was accepted as thirty days. Results: There were 183 candidaemia episodes among 179 adult patients with female predominance (67%) throughout all adult inpatients within the study period. Of these, 10 SOT recipients with female predominance (n=7) developed 11 candidaemia episodes: 6 episodes in 5 liver recipients, 4 episodes in 4 kidney recipients and 1 episode in 1 heart transplant recipient. The median age of SOT recipients at the time of candidaemia was 58 years (IQR: 26 y). Preinfection hospital stay and length of hospital stay did not differ statistically among C. albicans and non-albicans candidaemia groups. The source of candidaemia among SOT recipients was intraabdominal (6/11, 56%) predominantly occurring among liver recipients (67%). Although both the presence of central venous catheter (CVC) (91%) and total parenteral nutrition (82%) in the previous month before candidaemia were more commonly seen, CVC was the least source of candidaemia among SOT recipients. All transplant recipients with candidaemia had a history of antimicrobial therapy within the last month. Antifungal usage history was not statistically significantly associated with any of the Candida species (one of each: C. albicans, C. glabrata, C. lusitaniae, C. krusei). Concomitant bacterial bloodstream infections was detected in 46% of the candidaemia episodes. Crude mortality within first month after candidaemia was 46%. Discussion: The well known risk factors for infection due to Candida species are rejection episode, renal insufficiency, hepatic insufficiency, malnutrition, wide-spectrum antimicrobial use, abdominal surgery, total parenteral nutrition. The epidemiology of candidaemia changes geographically even among various centers in the same country. National TRANSNET surveillance study revealed that bloodstream was the most common infection site in invasive candidiasis among SOT recipients from 2001-2006. Conclusion: Candidaemia is a fatal medical emergency among all inpatients including SOT recipients. Continuous local and national surveillance will preserve its pivotal importance in therapeutic guidance of candidameia for all patient groups.